Investigating the Structural, Electronic and Magnetic Properties of Single Vanadium Atom Doped Germanene Monolayer using Density Functional Theory (DFT) - S. L., Usman; J. A, Owolabi; Shuaibu, Alhassan; M N, Maharaz (Physics Department, Faculty of Mathematics and Natural Sciences, University of Jember, 2024)
In this study, density functional theory (DFT) within generalized gradient approximation (GGA) as implemented in Quantum ESPRESSO package has been employed. The structural, electronic, and magnetic properties of single Vanadium atom (V)-doped germanene monolayer have been investigated. The doping is carried out in 2x2x1 supercell with 32 atoms which gives around 3.12% doping concentration. The results revealed that single V atom doped Germanene monolayer induced both ferromagnetic and antiferromagnetic behavior with total magnetic moment of about 0.77 μB and 1.95 μB respectively. Also the behavior of the pristine germanene remains unaffected by the single V doping. The stability of the doped system are investigated by calculating cohesive and binding energies. These results are in good agreement with many reported results in case of both graphene and silicene. It’s also suggested that, the single V-doped germanene monolayer can support the quantum anomalous Hall effect, which has significant potential for spintronic applications.Keyword: Density Functional Theory (DFT), Generalized Gradient Approximation (GGA), Structural, Electronic and Magnetic Properties, Doping, Germanene Monolayer